Neural oscillatory responses to performance monitoring differ between high‐ and low‐impulsive individuals, but are unaffected by TMS - Barth, Beatrix; Rohe, Tim; Deppermann, Saskia; Fallgatter, Andreas Jochen; Ehlis, Ann‐Christine (Human brain mapping, 2021)
Higher impulsivity may arise from neurophysiological deficits of cognitive control in the prefrontal cortex. Cognitive control can be assessed by time‐frequency decompositions of electrophysiological data. We aimed to clarify neuroelectric mechanisms of performance monitoring in connection with impulsiveness during a modified Eriksen flanker task in high‐ (n = 24) and low‐impulsive subjects (n = 21) and whether these are modulated by double‐blind, sham‐controlled intermittent theta burst stimulation (iTBS). We found a larger error‐specific peri‐response beta power decrease over fronto‐central sites in high‐impulsive compared to low‐impulsive participants, presumably indexing less effective motor execution processes. Lower parieto‐occipital theta intertrial phase coherence (ITPC) preceding correct responses predicted higher reaction time (RT) and higher RT variability, potentially reflecting efficacy of cognitive control or general attention. Single‐trial preresponse theta phase clustering was coupled to RT in correct trials (weighted ITPC), reflecting oscillatory dynamics that predict trial‐specific behavior. iTBS did not modulate behavior or EEG time‐frequency power. Performance monitoring was associated with time‐frequency patterns reflecting cognitive control (parieto‐occipital theta ITPC, theta weighted ITPC) as well as differential action planning/execution processes linked to trait impulsivity (frontal low beta power). Beyond that, results suggest no stimulation effect related to response‐locked time‐frequency dynamics with the current stimulation protocol. Neural oscillatory responses to performance monitoring differ between high‐ and low‐impulsive individuals, but are unaffected by iTBS. We aimed to clarify neuroelectric mechanisms of performance monitoring in connection with impulsiveness during a modified Eriksen flanker task in high‐ and low‐impulsive subjects. Performance monitoring was associated with time‐frequency patterns reflecting cognitive control (parieto‐occipital theta ITPC, theta weighted ITPC) as well as differential action planning/execution processes linked to trait impulsivity (frontal low beta power). Beyond that, results suggest no stimulation effect related to response‐locked time‐frequency dynamics with the current stimulation protocol.